Titi Laras Damina Educational Learning for Senior High School Students as a Form of Cultural Preservation - Kharisma Indah Dwi Putri Herdian; Rina Maryanti (Universitas Pendidikan Indonesia (UPI), 2023)
This study aims to educate Titi Laras Damina's learning in Kartika Senior High School students. The research was conducted on representatives of 10 grade-11 social studies students through 3 stages, namely (i) pre-test; (ii) theoretical and practical education using the Direct Instruction method; and (iii) post-test. The results showed that the average pretest theoretical value was 71 and the posttest average was 96.5. The results of the comparison of the pretest and posttest did not significantly increase after the learning was carried out. The results of the N-Gain calculation show that the average N-Gain value is 34% (N-Gain 40%) indicating that Titi Laras Damina's learning is theoretically ineffective for Senior High School students in grade 11 social studies. This is due to the comparison of pre-test scores. and the post-test was not so high and the students' knowledge was sufficient of Titi Laras theory. Practically there is a significant improvement because before learning students have not been able to mention the notes in each barrel. However, after learning using the direct instruction method there is an increase in musicality in students. Students can now say the notes in each barrel after it has been held. From this research, it is hoped that students can master the knowledge of Titi Laras Damina in theory and practice.